2008
DOI: 10.1002/tox.20452
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the copper sensitivity of two economically important saltwater mussel species and a review of previously reported copper toxicity data for mussels: Important implications for determining future ambient copper saltwater criteria in the USA

Abstract: Saltwater bivalves of the genus Mytilus are among the most copper sensitive taxa listed in both the current and recently proposed U.S. EPA ambient saltwater copper criteria documents. The copper saltwater quality criteria are somewhat unique in that the criteria were set specifically to protect Mytilus. However, there is considerable uncertainty in the reported taxonomy of Mytilus species in the criteria database and it has recently been demonstrated the copper toxicity to M. galloprovincialis is dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 21 publications
7
32
1
Order By: Relevance
“…Specimens from this culture have previously been genetically identified to confirm their taxonomy [16].…”
Section: Organism Sourcementioning
confidence: 99%
“…Specimens from this culture have previously been genetically identified to confirm their taxonomy [16].…”
Section: Organism Sourcementioning
confidence: 99%
“…Also, most of Arnold et al's prior work (e.g. Arnold et al, 2009 and documenting a DOC-dependent BLM bias on Cu toxicity to Mytilus sp. was performed with samples from San Francisco Bay.…”
Section: Introductionmentioning
confidence: 97%
“…As an example, in a study of Cu toxicity to Mytilus sp., Arnold et al (2005) have documented a DOC-dependent systematic bias between observed and BLM-predicted toxicity for estuarine and coastal waters, and they conclude that "the difference is likely due to errors in the BLM treatment of DOC". Since the BLM is essentially a variation on speciation calculation, this implies errors in the fundamental calculation that determines how much, and how strongly metals bind to DOC (Arnold et al, 2009 andNiyogi and Wood;and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations